The eye contact effect in request and emblematic hand gestures. (2nd December 2013) - Ferri, Francesca; Busiello, Marianna; Campione, Giovanna C.; De, Elisa; Innocenti, Alessandro; Romani, Gian Luca; Costantini, Marcello; Gentilucci, Maurizio
Abstract Request and emblematic gestures, despite being both communicative gestures, do differ in terms of social valence. Indeed, only the former are used to initiate/maintain/terminate an actual interaction. If such a difference is at stake, a relevant social cue, i.e. eye contact, should have different impacts on the neuronal underpinnings of the two types of gesture. We measured blood oxygen level‐dependent signals, using functional magnetic resonance imaging, while participants watched videos of an actor, either blindfolded or not, performing emblems, request gestures, or meaningless control movements. A left‐lateralized network was more activated by both types of communicative gestures than by meaningless movements, regardless of the accessibility of the actor's eyes. Strikingly, when eye contact was taken into account as a factor, a right‐lateralized network was more strongly activated by emblematic gestures performed by the non‐blindfolded actor than by those performed by the blindfolded actor. Such modulation possibly reflects the integration of information conveyed by the eyes with the representation of emblems. Conversely, a wider right‐lateralized network was more strongly activated by request gestures performed by the blindfolded than by those performed by the non‐blindfolded actor. This probably reflects the effect of the conflict between the observed action and its associated contextual information, in which relevant social cues are missing.